Возможности социально-педагогической реабилитации учащихся с нарушениями слуха средствами виртуальной музейной работы - Файтарон, М.
The article presented new approaches about possibilities of social and pedagogical rehabilitation of students with hearing disorders through virtual museum work . As part of involving students with hearing impairments in the world of culture, there is a need not only for the teacher’s extensive knowledge, but also for communication tools for working with persons with disabilities, as well as for the technologies of museum pedagogy.
Keywords: Социально-педагогическая реабилитация